A Survey of Overconfidence Investor Generation Y - wish, wisudanto (Advances in Social Sciences Research Journal, 2016)
Generation Y is a generation that has a unique, have different behavior with the previous generation and considerably larger than Generation X. In the case of investments, during the next five to ten years generation Y potential to become the biggest investor in the capital market, and who can understand the behavior of their investment will benefit. This study aims to determine Overconfidence investors generation Y. Overconfidence level of capital market investors was measured using Calibration assessment test. Assessment aimed at Generation Y, who is studying at the University and has become an investor in the capital market. The results could represent how overconfidence level of generation Y, which has the potential to become the largest investor in the total population.